Penerapan Climate Budget Tagging Menuju Penggunaan Anggaran yang Berkelanjutan - Maulidiyah, Syafrina; Akhmadi, Muhammad Heru (Sosio e-Kons, 2024)
Climate change is an issue that has become a topic of discussion at the international level. The Indonesian government displays a serious commitment to addressing climate change. Indonesia has initiated a commitment to reduce greenhouse gas emissions in the 2015-2019 Medium Term Development Plan (RPJMN) and low carbon development in the 2020-2024 RPJMN as well as enabling a commitment to reduce emissions in the Enhanced Nationally Determined Contribution (ENDC) to the UNFCCC by The emission reduction target is 31.89% below the Business as Usual (BAU) emission level with domestic resources and 43.20% below the BAU emission level with international support in 2030. One of the policies implemented by the Indonesian Government is Climate Budget Tagging (CBT), which is a form of support from the Ministry of Finance for mitigation and adaptation measures to climate change and low-carbon economic development with the principles of sustainable finance. This research uses qualitative methods through the interpretation of secondary data obtained through literature reviews, such as previous research studies and official websites. The CBT policy has been implemented in several Ministries/Institutions and Regional Governments in Indonesia. There are several obstacles in implementing CBT policies in Indonesia. Therefore, there are several policy recommendations in the context of maintaining CBT in Indonesia, such as increasing creative financing, and increasing coordination and integration of sites between Ministries/Agencies, Regional Governments and the Private Sector.